2018
DOI: 10.2147/ijn.s164097
|View full text |Cite
|
Sign up to set email alerts
|

Polyethyleneimine modification of aluminum hydroxide nanoparticle enhances antigen transportation and cross-presentation of dendritic cells

Abstract: BackgroundThe aim of this study was to explore the feasibility of delivering tumor antigens and enhancing the antigen cross-presentation of dendritic cells (DCs) by aluminum hydroxide nanoparticle with polyethyleneimine (PEI) modification (LV@HPA/PEI).Materials and methodsThe LV@HPA nanoparticles were modified by PEI first, then the influence of LV@HPA/PEI on DCs was examined. The distinct expression of ovalbumin (OVA) protein transported into DCs by LV@HPA/PEI was observed by flow cytometry and Western blot. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 41 publications
(39 reference statements)
1
20
0
Order By: Relevance
“…Changing size and surface chemistry of NPs were effective ways to regulate their effects on antigen cross-presentation intensity of DCs ( 118 , 119 ). Some metal oxide NPs such as aluminum hydroxide ( 120 ) and super-paramagnetic iron oxide NPs (SPIONs) ( 121 ) were also reported to improve the cross-presentation ability of DCs. These above studies suggested a potential strategy of using nanotechnology to develop DCs-based cancer immunotherapy.…”
Section: Nps Affect DC Functionsmentioning
confidence: 99%
“…Changing size and surface chemistry of NPs were effective ways to regulate their effects on antigen cross-presentation intensity of DCs ( 118 , 119 ). Some metal oxide NPs such as aluminum hydroxide ( 120 ) and super-paramagnetic iron oxide NPs (SPIONs) ( 121 ) were also reported to improve the cross-presentation ability of DCs. These above studies suggested a potential strategy of using nanotechnology to develop DCs-based cancer immunotherapy.…”
Section: Nps Affect DC Functionsmentioning
confidence: 99%
“…Coating materials play critical roles in the stabilization and subsequent functionalization of aqueous SPIO suspensions [15]. In previous studies, positively charged SPIO were shown to facilitate the cross-presentation ability of DCs to enhance the immune response, and they surpassed the effect of their oppositely charged counterparts [16, 17]. The mechanism through which differently charged SPIO can affect the antigen cross-presentation of DCs has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 TAAs expressed on cancer cells are the targets for the immune system, it can be processed and presented by professional antigen-presenting cells (pAPCs) such as DCs, and then trigger antigen-specific T cell immune responses to kill tumor cells. 22,33,34 Inactivated whole tumor cells or tumor cell lysates were kept as a source of TAAs in many therapeutic vaccines due to their numerous TAAs contained. This rich source of antigens contains multiple T-cell epitopes, which could elicit a stronger overall anti-tumor response.…”
Section: Discussionmentioning
confidence: 99%